Interferon-α signaling promotes embryonic HSC maturation - Kim, Peter Geon (Blood, 2016)
In the developing mouse embryo, the first hematopoietic stem cells (HSCs) arise in the aorta-gonad-mesonephros (AGM) and mature as they transit through the fetal liver (FL). Compared with FL and adult HSCs, AGM HSCs have reduced repopulation potential in irradiated adult transplant recipients but mechanisms underlying this deficiency in AGM HSCs are poorly understood. By co-expression gene network analysis, we deduced that AGM HSCs show lower levels of interferon-α (IFN-α)/Jak-Stat1–associated gene expression than FL HSCs. Treatment of AGM HSCs with IFN-α enhanced long-term hematopoietic engraftment and donor chimerism. Conversely, IFN-α receptor–deficient AGMs (Ifnαr1(−/−)), had significantly reduced donor chimerism. We identify adenine-thymine–rich interactive domain-3a (Arid3a), a factor essential for FL and B lymphopoiesis, as a key transcriptional co-regulator of IFN-α/Stat1 signaling. Arid3a occupies the genomic loci of Stat1 as well as several IFN-α effector genes, acting to regulate their expression. Accordingly, Arid3a(−/−) AGM HSCs had significantly reduced transplant potential, which was rescued by IFN-α treatment. Our results implicate the inflammatory IFN-α/Jak-Stat pathway in the developmental maturation of embryonic HSCs, whose manipulation may lead to increased potency of reprogrammed HSCs for transplantation.